The many facets of the banana tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The fruit can be served up as a puree, snack (dried slices and chips in Honduras and Nigeria), jam, vinegar, in bread, beer (Uganda), ketchup (Philippines), and baby food. It is also commonly found in muesli cereal mixes in Europe.The peel or 'skin'...